(untitled) (Лучшие интеллектуальные исследования, 2025)
Abstract: This study evaluates the suitability of three empirical models—Page, Exponential, and Logarithmic—for describing moisture loss in licorice root slices of varying sizes during hot air drying. Model performance was assessed through residual analysis, revealing the Logarithmic model as the most accurate across size categories. Differences in model fit were interpreted through morphological variation, suggesting that internal structure significantly influences drying behavior. The findings support a morphology-informed approach to selecting drying models and optimizing licorice processing.